Incorporating Task-Based and Cooperative Learning Strategies in an Introductory CLIL Microeconomics Class for Students at the Tertiary Level - Altamirano-Pazmiño, Alberto Fabián (My University, 2019)
The 21st century has brought a myriad of changes, of which one of the most influential has been the use of the English language as a lingua franca in education, business and social networking. These events have made learning English a global imperative in the furtherance of these opportunities which in turn enhances quality of life of the end-user and the country in a macro sense. Since 2012, in Ecuador, the government has incentivized its people to study abroad however, the level of English language teaching and learning in the country has not reached international standards due to lags and a lack of appropriate methodologies and the fact that English is not an official language in the country. A revolutionary approach to language teaching and learning is required and Content and Language Integrated Learning, which is considered the most effective way of foreign language teaching, was used to accomplish this purpose by focusing on the teaching of content rather than concentrating on language which is learned incidentally. Task-based and cooperative learning were applied in order to provide innovative strategies to content learning through a foreign language by focusing on student-centered and group-oriented class sessions which has shown to increase 21st century skills as well as language proficiency. This study proposes creating an intervention proposal to teach an introductory microeconomics course to tertiary level students using a CLIL approach and focusing on task based and cooperative learning techniques which will allow the student to gain an effective and long-lasting control of the English language and prepare them to become global citizens by enhancing the possibilities to study and work abroad.
Keywords: Content and language integrated learning; microeconomics; English as foreign language; task-based learning; cooperative learning; Máster Universitario en Educación Bilingüe